Effect of pH on nutrient removal and crop production of hydroponic systems treating brewery effluent - Richard P. Taylor (IWA Publishing, 2021)
The use of a crop to remove nutrients from brewery effluent and the influence of pH on these removal rates was evaluated. Cabbage (Brassica oleracea) was grown in recirculating hydroponic systems fed with post-anaerobically digested brewery effluent (BE) either subject to pH adjustment (6.5–7.0) or unaltered pH (8.0–8.5). These were compared with cabbages grown in water only and in a inorganic fertiliser nutrient solution (NS). Hydroponic systems fed with pH adjusted BE removed significantly more nitrogen and phosphorus than systems fed with pH unadjusted BE (p < 0.05). The final weight of cabbages from the pH adjusted BE systems were 6.7 times greater than cabbages from the pH unadjusted BE systems, whereas pH adjustment had no influence on cabbage weight in the water-only and NS treatments. Anaerobically digested BE that is not pH adjusted is not a suitable water and nutrient source for the hydroponic production of cabbages. However, pH adjustment of BE renders it more suitable for hydroponic crop production with hydroponic systems decreasing dissolved inorganic nitrogen, ammonium, phosphate and chemical oxygen demand concentrations by 72.8, 31.8, 98.5 and 51.0%, respectively. Hydroponic systems can be used to treat post-anaerobically digested BE to a similar standard obtained by conventional activated sludge treatment system. HIGHLIGHTS Effluent pH adjustment increased cabbage mass.; Effluent pH adjustment increased nutrient removal by cabbage plants.; Effluent pH adjustment increased the nitrogen concentration of cabbage leaves.; Hydroponic systems can be used to remove nutrients from pH adjusted effluent.;